PKM SOSIALISASI PENGARUH DAN DAMPAK GAMES PADA USIA DINI DI LINGKUNGAN RT.004 CIPAYUNG JAKARTA TIMUR: PKM SOSIALISASI PENGARUH DAN DAMPAK GAMES PADA USIA DINI DI LINGKUNGAN RT.004 CIPAYUNG JAKARTA TIMUR - Muhammad Tri Habibie; Bertha Meyke Waty Hutajulu; Reko Syarif Hidayatullah (Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this Community Service Socialization is to find out whether. There is a relationship between family functioning and self-control in children at an early age in the RT.004 Cipayung Jakarta Timur environment, who play games online. This research uses a case study method and a research approach qualitative research to obtain information about playing games at an early age in the Covid-19 pandemic. Interviews were conducted by asking respondents one by one, the results show that the level of achievement has decline and there is a new learning trend. Online learning causes students and parents adapt to this learning model. Besides, playing games on mobile is also the most favorite game during this pandemic.